Leukocyte-associated Ig-like receptor-1 is a novel inhibitory receptor for surfactant protein D. Issue 1 (28th February 2014) - Olde Nordkamp, Marloes J M; van Eijk, Martin; Urbanus, Rolf T; Bont, Louis; Haagsman, Henk P; Meyaard, Linde
Abstract : Inhibitory LAIR-1 as a novel receptor for SP-D, and may mediate immunomodulatory effects of SP-D. ABSTRACT: The collagenous C-type lectin, SP-D, is a multitrimeric glycoprotein present at mucosal surfaces and is involved in host defense against infections in mammals. SP-D has immunomodulatory properties, but the underlying mechanisms are incompletely understood. SP-D contains collagen domains. LAIR-1 is an inhibitory immune receptor at the cell surface of various immune-competent cells that binds collagen. We hypothesized that the immunomodulatory functions of SP-D can be mediated via interactions between its collagen domain and LAIR-1. Binding assays show that SP-D interacts via its collagenous domain with LAIR-1 and the related LAIR-2. This does not affect the mannan-binding capacities of SP-D, which induces cross-linking of LAIR-1 in a cellular reporter assay. Functional assays show that SP-D inhibits the production of FcαR-mediated reactive oxygen via LAIR-1. Our studies indicate that SP-D is a functional ligand of the immune inhibitory receptor LAIR-1. Thus, we have identified a novel pathway for the immunomodulatory functions of SP-D mediated via binding of its collagenous domains to LAIR-1. This may provide a mechanism for the unexplained immunomodulatory function of the collagenous domains of SP-D.